Diarrhoea‐causing enteric protist species in intensively and extensively raised pigs (Sus scrofa domesticus) in Southern Spain. Part II: Association with Hepatitis E virus susceptibility. Issue 4 (10th December 2021) - Rivero‐Juárez, Antonio; Dashti, Alejandro; Santín, Mónica; Köster, Pamela C.; López‐López, Pedro; Risalde, María A.; García‐Bocanegra, Ignacio; Gómez‐Villamandos, José Carlos; Caballero‐Gómez, Javier; Frías, Mario; Bailo, Begoña; Ortega, Sheila; et al.
Abstract: Enteropathogenic parasites can infect a wide range of mammals, including humans, supposing an important zoonotic risk. Hepatitis E virus (HEV) is an emerging foodborne pathogen of increasing public health relevance, affecting both humans and animal populations. Because both microorganisms share faecal‐oral transmission route they may constitute an excellent model to evaluate the interplay between them. Thus, we aim to evaluate the viral‐parasite interactions at the enteric interface in swine. We included pigs of two different breeds farming in South Spain under different production systems. We compared the HEV prevalence by the presence of Giardia duodenalis, Cryptosporidium spp., Balantioides coli, Blastocystis sp. and Enterocytozoon bieneusi in faecal samples. The HEV prevalence was 13.1 (62 out 475, 95% CI: 10.2–16.4). Those pigs infected with Cryptosporidium spp. showed a higher prevalence of HEV (30.8 vs . 12%; p  = .012). In the same way, animals bearing E. bieneusi seem to have a higher rate of HEV infection (24.2 vs . 12.2%; p  = .06). According to their location in the gut, animals bearing intracellular enteroparasites showed a higher HEV prevalence than those uninfected (29.6 vs . 12.7%; p  = .038), meanwhile those carrying extracellular enteroparasites had a lower likelihood to be infected by HEV than those uninfected (12.1 vs . 23.1%; p  = .071). Those animals bearing both types of enteroparasites showed a similar prevalence of HEV infection than those exhibiting negative for both (20.8 vs . 26.1%; p  = .763). Our study provides evidence that intracellular and extracellular enteroparasites modulate the susceptibility to HEV infection in pigs. Meanwhile, the presence of extracellular enteroparasites shows a protective effect on the risk of HEV acquisition in swine, whereas intracellular enteroparasites seems to have the opposite effect, favouring the HEV infection.